PENGEMBANGAN E-MODUL BERBANTUAN HEYZINE FLIPBOOK DALAM MATERI BANGUN DATAR DI SEKOLAH DASAR - Lusiyawati Lusiyawati; Yuli Mulyawati; Santa Santa (CV. ADIBA AISHA AMIRA, 2025)
Development of E-Modules Assisted by Heyzine Flipbook in Flat Buildings Material at Elementary School. This study uses a Research and Development (RnD) approach. The research subjects were class IV-A students of Police 1 State Elementary School in Bogor City consisting of 22 students, the research was conducted in the even semester of the 2023/2024 academic year. This development research uses the ADDIE method which consists of five stages, namely analysis, design, development, implementation, and evaluation. Based on the results of the study, it can be concluded that the e-module assisted by heyzine flipbook in flat building material in this study is proven to be valid, interesting, easy to use and feasible to apply as a learning tool.